The relationships of employer branding towards final year students interest to work in Indonesian startup companies (case study of business economics and engineering students in ITB and UI, Indonesia) - Ramadhan, Al Fathan; Pritasari, Adita (Journal of Business and Management, 2020)
Abstract. Employer Branding is an image of Companies used as a tool to gain interest for employee candidates to work in the company. At the same time, many companies compete with each other to find the best candidates, especially for Startup Company. Nowadays, Generation Z is entering the new workforce. They have different characteristics than the previous generation, and most of them are in their final year in universities. The objective of this research is to find the suitable Employer Branding for Startup Companies to increase the Final Year Students' interest to apply. This research's scope is the Business Economics and Engineering cluster in ITB and UI, Indonesia. This research uses primary and secondary data from an online questionnaire gathered from 273 respondents and previous studies. PCA (Principal Component Analysis) was used to process the data. The result of this research shows the dominant factors of Employer Branding for each university and cluster are not similar. Transparency, Fringe Benefit and Interesting Job are the factors that are most dominant and corresponding with the Generation Z characteristics. While contradicting with Generation Z characteristics, Digital Savvy is not mentioned in Employer Branding since the technology may be considered as something that the company should have.Keywords: Generation Z, Employer Branding, Final Year Students, Startup Company